2018
DOI: 10.1021/acs.jafc.8b03174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Delivery System Type on Curcumin Bioaccessibility: Comparison of Curcumin-Loaded Nanoemulsions with Commercial Curcumin Supplements

Abstract: In this study, nanoemulsion-based delivery systems fabricated using three different methods were compared with three commercially available curcumin supplements. Powdered curcumin was dispersed into the oil-in-water nanoemulsions using three methods: the conventional oil-loading method, the heat-driven method, and the pH-driven method. The conventional method involved dissolving powdered curcumin in the oil phase (60 °C, 2 h) and then forming a nanoemulsion. The heat-driven method involved forming a nanoemulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 46 publications
1
91
0
Order By: Relevance
“…At pH values around and above the pK a values of its hydroxyl groups, curcumin undergoes rapid hydrolytic degradation, which has been attributed to cleavage of the α, β-unsaturated β-diketone moiety. As a result, the original curcumin molecule is transformed into trans-6-(4′-hydroxy-3′-methoxyphenyl)-2,4-dioxo-5-hexanal, which itself undergoes cleavage reactions to form ferulic acid, feruloylmethane, and vanillin [ 4 , 13 , 53 , 54 ] ( Figure 2 ). The color of curcumin fades due to this alkaline degradation reaction.…”
Section: Factors Affecting Curcumin’s Applicationmentioning
confidence: 99%
“…At pH values around and above the pK a values of its hydroxyl groups, curcumin undergoes rapid hydrolytic degradation, which has been attributed to cleavage of the α, β-unsaturated β-diketone moiety. As a result, the original curcumin molecule is transformed into trans-6-(4′-hydroxy-3′-methoxyphenyl)-2,4-dioxo-5-hexanal, which itself undergoes cleavage reactions to form ferulic acid, feruloylmethane, and vanillin [ 4 , 13 , 53 , 54 ] ( Figure 2 ). The color of curcumin fades due to this alkaline degradation reaction.…”
Section: Factors Affecting Curcumin’s Applicationmentioning
confidence: 99%
“…Zheng et al [77] subjected CUR loaded oil-in-water (O/W) NEs prepared using the conventional oil-loading method, the heat-driven method, and the pH-driven method and three commercial CUR supplements (Nature Made, Full Spectrum, and CurcuWin) to a simulated GI tract model consisting of mouth, stomach, and small intestine phases and found that the three tested NEs showed similar CUR bioaccessibility (74–79%) with the highest absolute amount of CUR in the mixed micelle phase of the NE fabricated by the pH-driven method. The concentration of CUR in mixed micelles decreased as follows: CurcuWin ≈ pH-driven method > heat-driven method > conventional method >> full spectrum > nature made, and CUR encapsulated in small lipid particles had an improved absorption in GI tract.…”
Section: Types Of Formulations and Used Materialsmentioning
confidence: 99%
“…Various delivery and encapsulation systems had been developed for curcumin. Among these, lipidbased system allowed a higher loading capacity, such as nanoemulsion, liposomes and nanoparticles (Wang et al, 2013;Martin et al, 2017;Silva et al, 2017;Zheng et al, 2018). Although these investigations have improved the solubility and bioactivity of curcumin to some extent, their preparation technique is relatively complex and they are prone to polymorphic rearrangements and changes in crystallinity which affect the stability of bioactives (Tadros et al, 2004;O'Sullivan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%